You are on page 1of 16

ONE-SCHOOL.

NET

Add Maths Formulae List: Form 4 (Update 18/9/08)


01 Functions
Absolute Value Function Inverse Function If

f ( x ), if f ( x ) 0 f ( x)
f ( x), if f ( x ) < 0

y = f ( x ) , then f 1 ( y ) = x

Remember: Object = the value of x Image = the value of y or f(x) f(x) map onto itself means f(x) = x

02 Quadratic Equations
General Form Quadratic Formula

ax 2 + bx + c = 0
where a, b, and c are constants and a 0. *Note that the highest power of an unknown of a quadratic equation is 2. Forming Quadratic Equation From its Roots: If and are the roots of a quadratic equation

b b 2 4ac x= 2a
When the equation can not be factorized. Nature of Roots

+ =

b a

c a

The Quadratic Equation

x 2 ( + ) x + = 0
or x ( SoR ) x + ( PoR ) = 0 SoR = Sum of Roots PoR = Product of Roots
2

b 2 4ac b 2 4ac b 2 4ac b 2 4ac

>0 =0 <0 0

two real and different roots two real and equal roots no real roots the roots are real

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
03 Quadratic Functions
General Form Completing the square:

f ( x) = ax 2 + bx + c where a, b, and c are constants and a 0. *Note that the highest power of an unknown of a quadratic function is 2. (i) (ii) (iii) (iv)

f ( x) = a ( x + p)2 + q the value of x, x = p min./max. value = q min./max. point = ( p, q) equation of axis of symmetry, x = p

Alternative method:
a > 0 minimum (smiling face)
a < 0 maximum (sad face)

f ( x) = ax 2 + bx + c (i) the value of x, x =

b 2a b ) 2a b 2a

(ii) (iii)
Quadratic Inequalities
a > 0 and f ( x) > 0 a > 0 and f ( x) < 0

min./max. value = f (

equation of axis of symmetry, x =

Nature of Roots

a
a< x<b

intersects two different points at x-axis 2 b 4ac = 0 touch one point at x-axis b 2 4ac < 0 does not meet x-axis
b 2 4ac > 0

x < a or x > b

04 Simultaneous Equations
To find the intersection point solves simultaneous equation. Remember: substitute linear equation into non- linear equation.

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
05 Indices and Logarithm
Fundamental if Indices Laws of Indices

Zero Index, Negative Index,

a0 = 1

a m a n = a m+n a m a n = a mn
( a m ) n = a m n ( ab) n = a n b n
m

a 1 =

1 a

a b ( ) 1 = b a Fractional Index
1 an

= a
n

m an

= a
n

a n an ( ) = n b b
Law of Logarithm

Fundamental of Logarithm

log a y = x a x = y
log a a = 1

log a mn = log a m + log a n

log a

log a a x = x
log a 1 = 0

m = log a m log a n n

log a mn = n log a m
Changing the Base

log a b =

log c b log c a

log a b =

1 logb a

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
06 Coordinate Geometry
Distance and Gradient
Distance Between Point A and C =

(x1 x2 )2 + (x1 x2 )2
Gradient of line AC, m = Or
y int ercept Gradient of a line, m = x int ercept y2 y1 x2 x1

Parallel Lines

Perpendicular Lines

When 2 lines are parallel,

When 2 lines are perpendicular to each other,


m1 m2 = 1

m1 = m2 .

m1 = gradient of line 1 m2 = gradient of line 2

Midpoint

A point dividing a segment of a line

Midpoint, M =

x1 + x2 y1 + y2 , 2 2

A point dividing a segment of a line

nx + mx2 ny1 + my2 P = 1 , m+n m+n

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
Area of triangle:

Area of Triangle

1 2
1 ( x1 y2 + x2 y3 + x3 y1 ) ( x2 y1 + x3 y2 + x1 y3 ) 2

A=

Form of Equation of Straight Line General form


ax + by + c = 0

Gradient form
y = mx + c

Intercept form

m = gradient c = y-intercept

x y + =1 a b a = x-intercept b = y-intercept m= b a

Equation of Straight Line Gradient (m) and 1 point (x1, y1) 2 points, (x1, y1) and (x2, y2) given given y y1 y2 y1 y y1 = m( x x1 ) = x x1 x2 x1

x-intercept and y-intercept given x y + =1 a b

Equation of perpendicular bisector gets midpoint and gradient of perpendicular line.


Information in a rhombus: A

(i) (ii) (iii) (iv)

same length AB = BC = CD = AD parallel lines mAB = mCD or mAD = mBC diagonals (perpendicular) mAC mBD = 1 share same midpoint midpoint AC = midpoint BD any point solve the simultaneous equations

(v)

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
Remember:

y-intercept x = 0 cut y-axis x = 0 x-intercept y = 0 cut x-axis y = 0 **point lies on the line satisfy the equation substitute the value of x and of y of the point into the equation.

Equation of Locus ( use the formula of distance) The equation of the locus of a moving point P ( x, y ) which is always at a constant distance (r) from a fixed point A ( x1 , y1 ) is

The equation of the locus of a moving point P ( x, y ) which is always at a constant distance from two fixed points A ( x1 , y1 ) and B ( x2 , y 2 ) with a ratio m : n is PA m = PB n

The equation of the locus of a moving point P ( x, y ) which is always equidistant from two fixed points A and B is the perpendicular bisector of the straight line AB. PA = PB ( x x1 ) + ( y y1 ) 2 = ( x x2 ) 2 + ( y y2 ) 2
2

PA = r

( x x1 ) 2 + ( y y1 ) 2 = r 2

( x x1 ) 2 + ( y y1 ) 2 m 2 = ( x x2 ) + ( y y 2 ) 2 n 2

More Formulae and Equation List: SPM Form 4 Physics - Formulae List SPM Form 5 Physics - Formulae List SPM Form 4 Chemistry - List of Chemical Reactions SPM Form 5 Chemistry - List of Chemical Reactions

All at One-School.net

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
07 Statistics
Measure of Central Tendency Ungrouped Data Mean
x= x N

Without Class Interval


x= fx f

Grouped Data With Class Interval


x= x = mean f = frequency x = class mark fx f

x = mean x = sum of x x = value of the data


N = total number of the data

x = mean x = sum of x f = frequency x = value of the data

(lower limit+upper limit) 2

Median

m = TN +1
2

m = TN +1
2

When N is an odd number.

When N is an odd number.

1N F C m = L+ 2 f m
m = median L = Lower boundary of median class N = Number of data F = Total frequency before median class fm = Total frequency in median class c = Size class = (Upper boundary lower boundary)

TN + TN m=
2 2

+1

TN + T N m=
2 2

+1

When N is an even number.

When N is an even number.

Measure of Dispersion Ungrouped Data Grouped Data Without Class Interval With Class Interval

variance

x2 =
2

fx 2 = f
2

fx 2 = f
2

= variance
Standard Deviation
(x x ) = N
2

= variance
= =
(x x ) N x 2 x2 N
2

= variance
f (x x) = f
2

x 2 x2 N

fx 2 x2 f

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
The variance is a measure of the mean for the square of the deviations from the mean. The standard deviation refers to the square root for the variance.
Effects of data changes on Measures of Central Tendency and Measures of dispersion Data are changed uniformly with +k k k k +k k k k

Measures of Mean, median, mode Central Tendency Range , Interquartile Range Measures of Standard Deviation dispersion Variance

No changes No changes No changes

k k k2

k k k2

08 Circular Measures
Terminology

Convert degree to radian: Convert radian to degree:

radians

180

degrees

)radians 180 180 ) degrees x radians = ( x

xo = ( x

180

Remember:

180 = rad ??? 360 = 2 rad


0.7 rad

O ???

1.2 rad

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
Length and Area

r = radius A = area s = arc length = angle l = length of chord

Arc Length:

Length of chord:

Area of Sector:

Area of Triangle:

Area of Segment:

s = r

l = 2r sin

A=

1 2 r 2

A=

1 2 r sin 2

A=

1 2 r ( sin ) 2

09 Differentiation
Gradient of a tangent of a line (curve or straight)
dy y = lim ( ) dx x 0 x
Differentiation of a Function I

y = xn dy = nx n1 dx
Example y = x3

Differentiation of Algebraic Function Differentiation of a Constant

dy = 3x 2 dx

y=a dy =0 dx

a is a constant
Differentiation of a Function II
y = ax dy = ax11 = ax 0 = a dx

Example y=2 dy =0 dx

Example y = 3x dy =3 dx

http://www.one-school.net/notes.html

ONE-SCHOOL.NET
Differentiation of a Function III Chain Rule

y = ax n dy = anx n1 dx
Example y = 2 x3

y = un

u and v are functions in x

dy dy du = dx du dx
Example y = (2 x 2 + 3)5
u = 2 x 2 + 3, y = u5 , therefore du = 4x dx

dy = 2(3) x 2 = 6 x 2 dx
Differentiation of a Fractional Function
1 xn Rewrite y= y = xn dy n = nx n1 = n+1 dx x

therefore

dy = 5u 4 du

dy dy du = dx du dx = 5u 4 4 x = 5(2 x 2 + 3) 4 4 x = 20 x(2 x 2 + 3) 4

Or differentiate directly y = (ax + b) n

Example 1 y= x y = x 1 dy 1 = 1x 2 = 2 dx x

dy = n.a.(ax + b) n 1 dx

y = (2 x 2 + 3)5 dy = 5(2 x 2 + 3) 4 4 x = 20 x(2 x 2 + 3) 4 dx

Law of Differentiation Sum and Difference Rule

y =uv u and v are functions in x dy du dv = dx dx dx Example y = 2 x3 + 5 x 2

dy = 2(3) x 2 + 5(2) x = 6 x 2 + 10 x dx

http://www.one-school.net/notes.html

10

ONE-SCHOOL.NET
Product Rule Quotient Rule
y= u v v u and v are functions in x du dv u dx dx v2

y = uv u and v are functions in x dy du dv = v +u dx dx dx Example y = (2 x + 3)(3 x 3 2 x 2 x)


u = 2x + 3 v = 3x3 2 x 2 x du dv =2 = 9 x2 4 x 1 dx dx dy du dv =v +u dx dx dx 3 2 =(3 x 2 x x)(2) + (2 x + 3)(9 x 2 4 x 1)

dy = dx

Or differentiate directly y = (2 x + 3)(3x3 2 x 2 x)

dy = (3x3 2 x 2 x)(2) + (2 x + 3)(9 x 2 4 x 1) dx

Example x2 y= 2x +1 u = x2 v = 2x +1 du dv = 2x =2 dx dx du dv u v dy = dx 2 dx dx v dy (2 x + 1)(2 x) x 2 (2) = dx (2 x + 1) 2


4 x2 + 2 x 2 x2 2 x2 + 2 x = = (2 x + 1) 2 (2 x + 1) 2

Or differentiate directly x2 y= 2x +1 dy (2 x + 1)(2 x) x 2 (2) = dx (2 x + 1) 2


4 x2 + 2 x 2 x2 2 x2 + 2 x = = (2 x + 1) 2 (2 x + 1) 2

http://www.one-school.net/notes.html

11

ONE-SCHOOL.NET
Gradients of tangents, Equation of tangent and Normal Gradient of tangent at A(x1, y1):

dy = gradient of tangent dx Equation of tangent: y y1 = m( x x1 )


Gradient of normal at A(x1, y1):
mnormal = 1 mtangent

If A(x1, y1) is a point on a line y = f(x), the gradient of the line (for a straight line) or the gradient of the dy tangent of the line (for a curve) is the value of dx when x = x1.

dx Equation of normal : y y1 = m( x x1 )

1 dy

= gradient of normal

Maximum and Minimum Point

Turning point At maximum point, dy =0 dx

dy =0 dx

d y <0 dx 2

At minimum point , dy =0 dx

d2y >0 dx 2

http://www.one-school.net/notes.html

12

ONE-SCHOOL.NET
Rates of Change Small Changes and Approximation Small Change:

Chain rule

dA dA dr = dt dr dt

y dy dy y x x dx dx
Approximation: ynew = yoriginal + y

If x changes at the rate of 5 cms -1

dx =5 dt Decreases/leaks/reduces NEGATIVES values!!!

= yoriginal +

dy x dx

x = small changes in x y = small changes in y If x becomes smaller x = NEGATIVE

http://www.one-school.net/notes.html

13

ONE-SCHOOL.NET
10 Solution of Triangle

Sine Rule:
a b c = = sin A sin B sin C

Cosine Rule:
a2 = b2 + c2 2bc cosA b2 = a2 + c2 2ac cosB c2 = a2 + b2 2ab cosC

Area of triangle:
a

C
b

Use, when given 2 sides and 1 non included angle 2 angles and 1 side
B A 180 (A+B) a

cos A =

b2 + c2 a 2 2bc

A=

a A b

Use, when given 2 sides and 1 included angle 3 sides


a A b b c

1 a b sin C 2

C is the included angle of sides a and b.

http://www.one-school.net/notes.html

14

ONE-SCHOOL.NET
Case of AMBIGUITY
A
180 -

If C, the length AC and length AB remain unchanged, the point B can also be at point B where ABC = acute and A B C = obtuse. If ABC = , thus ABC = 180 .

Remember : sin = sin (180 )


Case 2: When a = b sin A CB just touch the side opposite to C

C B B Case 1: When a < b sin A CB is too short to reach the side opposite to C.

Outcome: No solution Case 3: When a > b sin A but a < b. CB cuts the side opposite to C at 2 points

Outcome: 1 solution Case 4: When a > b sin A and a > b. CB cuts the side opposite to C at 1 points

Outcome: 2 solution Useful information:


b a c

Outcome: 1 solution

In a right angled triangle, you may use the following to solve the problems. (i) Phythagoras Theorem: c = a 2 + b2 (ii) Trigonometry ratio: sin = b , cos = a , tan = c c
b a

(iii) Area = (base)(height)

http://www.one-school.net/notes.html

15

ONE-SCHOOL.NET
11 Index Number
Price Index Composite index

I =

P 1 100 P0

I=

Wi I i Wi

I = Price index / Index number


P0 = Price at the base time P1 = Price at a specific time

I = Composite Index W = Weightage I = Price index

I A, B I B ,C = I A,C 100

http://www.one-school.net/notes.html

16